A comparison study of high shear force and compatibilizer on the phase morphologies and properties of polypropylene/polylactide (PP/PLA) blends. (10th October 2018) - Sui, Guopeng; Jing, Mengfan; Zhao, Jing; Wang, Ke; Zhang, Qin; Fu, Qiang
Abstract: Exerting high shear force and adding compatilizer are two different methods used for regulating the size of dispersed phase of polymer blends. Nevertheless, the comparison of the effect of the high shear force and adding compatilizer on the phase morphologyies and properties is less studied, not to mention the synergistic effect. In this work, the incompatible PP/PLA binary blends with large polarity differences were prepared using high-shear processing, compared with the effect of adding ethylene-(methyl acrylate)-(glycidyl methacrylate) (EMA-GMA) as reactive compatibilizer for PP/PLA blends. It was found that adding compatilizer under relative low shear force was more efficient on improving the interface, showing blurred boundaries, compared with the reduction of the dispersed phase size under high shear force without compatilizer. As a result, the blends with the compatilizer presented a higher elongation at break; yet the yield strength of the binary blends prepared under high shear force was higher than that of the ternary blends. Furthermore, the synergistic effect of adding compatibilizer and high shear force was limited, which could be attributed to the fact that the degree of reactive compatibilization had already reached saturation under the rotation speed of 100 rpm due to the high efficiency of EMA-GMA. Graphical abstract: Highlights: The comparison of the effect of the high shear force and adding compatilizer is systematically studied. The size of the PLA dispersed droplets decreases significantly under high rotation speed and relatively low temperature. The PP/PLA binary blends prepared using high-shear processing show higher yield strength and lower toughness.